Ultrasound assisted deep eutectic solvent based microextraction-slotted quartz tube-flame atomic absorption spectrometry for the determination of cadmium - Unutkan, Tugce; Tisli, Busra; Tekin, Zeynep; Cetin, Gulten; Bakirdere, Sezgin (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This study made use of the unique extraction properties of deep eutectic solvents (DESs) to determine trace levels of cadmium by slotted quartz tube flame atomic absorption spectrometry (SQT-FAAS). Ultrasound assisted (UA)-DES was applied in this study to improve the detection limit. The optimum extraction conditions were 1:2 ratio of choline chloride and phenol as DES, 0.50 mL DES volume, 1.0 mL emulsifier agent volume and 10 s of manual mixing. The linear calibration range of the optimum method was between 1.0 and 50 mu g L-1. Combining the DES extraction method and SQT-FAAS gave 0.35 and 1.2 mu g L-1 as the limits of detection and quantitation (LOD and LOQ), respectively. The sensitivity was improved by about 80 folds when compared with the conventional FAAS system. Accuracy and applicability of the method were also checked using celery and apple samples, and the recovery results calculated were close to 100%, respectively.
Keywords: Cadmium; FAAS; SQT; Deep eutectic solvent; TRACE AMOUNTS; WATER; FOOD; Spectroscopy